2012
DOI: 10.1021/es3006207
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Phytochelatin Surface Display in Cupriavidus metallidurans CH34 for Enhanced Metals Bioremediation

Abstract: This work describes the effects of the cell surface display of a synthetic phytochelatin in the highly metal tolerant bacterium Cupriavidus metallidurans CH34. The EC20sp synthetic phytochelatin gene was fused between the coding sequences of the signal peptide (SS) and of the autotransporter β-domain of the Neisseria gonorrhoeae IgA protease precursor (IgAβ), which successfully targeted the hybrid protein toward the C. metallidurans outer membrane. The expression of the SS-EC20sp-IgAβ gene fusion was driven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 33 publications
(78 reference statements)
1
19
0
4
Order By: Relevance
“…There is abundant literature showing that metal resistant bacteria with high biosorption capacity enhance plant growth (Rodríguez-Llorente et al, 2010;Dary et al, 2010) but the information is scarce on the stage of germination. In this regard, genetic engineering of the bacterial cell surface has been carried out in order to enhance metal biosorption and increase plant protection against metals (Valls et al, 2000;Biondo et al, 2012). Furthermore, it is well known that different types of microorganisms (gram positive and gram negative bacteria, yeast, mycorrhizal fungi, algae, cyanobacteria, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…There is abundant literature showing that metal resistant bacteria with high biosorption capacity enhance plant growth (Rodríguez-Llorente et al, 2010;Dary et al, 2010) but the information is scarce on the stage of germination. In this regard, genetic engineering of the bacterial cell surface has been carried out in order to enhance metal biosorption and increase plant protection against metals (Valls et al, 2000;Biondo et al, 2012). Furthermore, it is well known that different types of microorganisms (gram positive and gram negative bacteria, yeast, mycorrhizal fungi, algae, cyanobacteria, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…52 Additionally, a comparison within Cupriavidus strains showed that the copper biosorption capacity of C. gilardii CR3 was almost the same as that of the C. taiwanensis TJ208 (19.0 mg g À1 ), whereas lower than that of C. metallidurans CH34 (26.69 mg g À1 ) under the same experiment conditions. 53 Therefore, it is still efficient compared to other bacteria in terms of copper biosorption capacity: the copper biosorption capacity of Bacillus sp. is 16.25 mg g À1 (ref.…”
Section: Isotherms Studymentioning
confidence: 99%
“…For environmentally relevant biotechnological applications however, a more robust host is needed. The use of a different host organism for such applications is nevertheless limited to a few reports addressing metal remediation with Cupriavidus metallidurans CH34 [9,10] or Pseudomonas putida [11] for which the researchers applied the heterologous AT IgA of Neisseria gonorrhoeae . The use of an autologous AT, instead of a heterologous AT, might however be more appropriate.…”
Section: Introductionmentioning
confidence: 99%